Macrofinancial Stress Testing : Principles and Practices. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
The recent financial crisis drew unprecedented attention to the stress testing of financial institutions. On one hand, stress tests were criticized for having missed many of the vulnerabilities that led to the crisis. On the other, after the onset of the crisis, they were given a new role as crisis management tools to guide bank recapitalization and help restore confidence. This spurred an intense debate on the models, underlying assumptions, and uses of stress tests. Current stress testing practices, however, are not based on a systematic and comprehensive set of principles but have emerged from trial-and-error and often reflect constraints in human, technical, and data capabilities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet